Sistem Pakar untuk Mendiagnosa Penyakit yang Disebabkan Nyamuk dengan Metode Forward Chainning - Nur Nafi’iyah; Endang Setyati (Jurnal Ilmiah Teknologi Informasi Asia, 2012)
Artificial Intellegence is an application used to assist in solving specific problems. The application of Artificial Intellegence is used to determine and to diagnose diseases caused by mosquitoes. This application is implemented by using Visual Basic 6.0 and MySql database. Data obtained through the international observation and analyzed using chainning forward method to trace the diseases caused by mosquitoes. Keywords: Artificial Intellegence, Forward Chainning, diseases caused by mosquitoes